Editorial: Group-Focused Enmity – Conceptual, Longitudinal, and Cross-National Perspectives Based on Pre-registered Studies - Friehs, Maria-Therese (International journal of conflict and violence, 2022)
Group-Focused Enmity describes the idea that different outgroup-specific prejudices can be aggregated to a larger syndrome of inequality-based derogation of others. This focus section brings together three studies on Group-Focused Enmity that had been registered and peer-reviewed before they were conducted. All of the reports advance the Group-Focused Enmity literature in important ways and demonstrate the fruitfulness of the concept. They also show that using sophisticated methods can help us to address novel and exciting questions, and demonstrate the opportunities that preregistration offers for studies analysing secondary data.